2015
DOI: 10.1080/1755876x.2015.1022067
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of observations on ocean forecasts and reanalyses: Part 1, Global studies

Abstract: h GODAE OceanView Observing System Evaluation Task TeamUnder GODAE OceanView the operational ocean modelling community has developed a suite of global ocean forecast, reanalysis and analysis systems. Each system has a critical dependence on ocean observations -routinely assimilating observations of in-situ temperature and salinity, and satellite sea-level anomaly and sea surface temperature. This paper demonstrates the value and impact of ocean observations to three global eddy-permitting forecast systems, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 37 publications
4
65
0
1
Order By: Relevance
“…This was also found in OSEs conducted with different real-time forecasting systems (e.g. Lea et al, 2014;Oke et al, 2015), where the first altimeter contributes the most to the sea level error reduction. Forecasts of sea level and ocean currents continue to be improved when moving from one altimeter to two altimeters with a relative error reduction of almost 30 %.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This was also found in OSEs conducted with different real-time forecasting systems (e.g. Lea et al, 2014;Oke et al, 2015), where the first altimeter contributes the most to the sea level error reduction. Forecasts of sea level and ocean currents continue to be improved when moving from one altimeter to two altimeters with a relative error reduction of almost 30 %.…”
Section: Discussionmentioning
confidence: 60%
“…OSEs carried out in the context of the GODAE OceanView international programme (Bell et al, 2015) have demonstrated the impact of assimilating several altimeters and Argo (e.g. Lea et al, 2014;Oke et al, 2015;Turpin et al, 2016). They show, in particular, that the addition of the first altimeter has the largest impact but that there are quantitative improvements seen by the addition of a second and third altimeter.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the OSE-TT is to produce coordinated and timely assessments of the impact of observing systems on the GOV forecasting systems and to communicate the results so that they are used to inform the maintenance and adaptation of the observing system. Very good progress has been made in this direction using global (Oke et al 2015a) and regional (Oke et al 2015b) prediction systems in the last five years and there is great potential for further progress.…”
Section: International Coordinationmentioning
confidence: 99%
“…Information about SST is required by scientific, commercial, and social interest activities [69], such as weather forecasting, air-sea interaction modeling, climate change studies, fisheries, and coastal zone management [44]. Figure 6 shows the monthly diurnal Sea Surface Temperature (dSST) from Karagali et al [44] as the mean hourly difference from the night-time reference SST from March to August.…”
Section: Sea Surface Temperaturementioning
confidence: 99%